Qualitative Analysis of Bank Dhofar SHRM Initiative - Kolluru, Mythili; MadhuSudhana Rao Kondaveeti, V.Ch. MadhuSudhana Rao Kondaveeti; Rahman Ali Al Balushi, Sana Adbul (International Journal of Psychosocial Rehabilitation, 2021)
Talent is a set of personal characteristics that enhance individual performance. This study explores the effectiveness of the talent management program "Al Mawahib" in achieving the Vision 2020 of Bank Dhofar. The bank, Oman's second-largest with 73 branches, launched a comprehensive strategic transformation plan that includes various initiatives and projects. As part of this, Bank Dhofar initiated the "Together 2020" strategic transformation plan to meet Vision 2020 goals. The HR department developed a talent management program to support the organization's objectives. The study traces the progress of the Al Mawahib talent development program and uses a qualitative research approach, conducting in-depth interviews with senior staff members. Content analysis was applied to analyze the interview data. The study reveals that the program targets young, potential leaders and aligns with Bank Dhofar's Vision 2020. The program has trained 170 employees, who will then train other employees in their branches, highlighting the unique aspect of this program.